Advertising as a distortion of social learning - Kjell Arne Brekke; Mari Rege (University of Oslo, Department of Economics, 2006)
By combining a theory of herding behavior with the phenomenon of availability heuristic, this paper shows that non-informative advertisements can affect people's choices by influencing their perception of product quality. We present a model in which people can learn about product quality by observing the choices of others. Consumers are, however, not able to fully distinguish between the observations of real people and fictitious characters in advertisements. Even if a person is aware of this limitation and updates his beliefs accordingly, it is still rational for him to choose the product he has observed most often. In equilibrium the most observed product is always most likely to be of the highest quality. The analysis has important policy implications.
Keywords: D21; L15; M37; 330; Advertising; availability heuristic; herding behavior; information; product quality; Werbung; Konsumentenverhalten; Herdenverhalten; Informationswert; Produktqualität; Theorie